2011
DOI: 10.1039/c1ra00491c
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4@SiO2@Pd-Au: a highly efficient and magnetically separable catalyst for liquid-phase hydrodechlorination of 4-chlorophenol

Abstract: was synthesized by reducing palladium and gold cations previously bound to the amine ligand-modified surface of silicaencapsulated magnetic iron oxide (Fe 3 O 4 ) nanoparticles, and served as a highly efficient and easily-recyclable catalyst for liquid-phase hydrodechlorination of 4-chlorophenol under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…[6][7][8][9] In recent years, nano-sized zero valent iron (nZVI) has been widely applied to treat a wide range of contaminants due to nZVI being cheap, abundant and non-toxic and possessing excellent chemical, surface and adsorptive properties. [10][11][12][13][14][15] However, using nZVI for remediation of contaminated wastewater is limited due to its lack of stability, easy aggregation and easy passivation and the poor retrievability of nZVI from the treated solution. [16][17][18][19][20] Various nZVI based bimetallic catalysts were developed to study the reductive dechlorination of COC contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In recent years, nano-sized zero valent iron (nZVI) has been widely applied to treat a wide range of contaminants due to nZVI being cheap, abundant and non-toxic and possessing excellent chemical, surface and adsorptive properties. [10][11][12][13][14][15] However, using nZVI for remediation of contaminated wastewater is limited due to its lack of stability, easy aggregation and easy passivation and the poor retrievability of nZVI from the treated solution. [16][17][18][19][20] Various nZVI based bimetallic catalysts were developed to study the reductive dechlorination of COC contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have demonstrated the synthesis of various magnetic silica-coated nanostructures [66][67][68][69]. Notably, Moon and Hyeon [66] synthesized Fe3O4@mSiO2 particles with tunable diameters of 45, 60, 90, and 105 nm by varying the concentration of the core nanocrystal during the formation of the mesoporous silica shell.…”
Section: Magnetic Core-shell Nanocatalysts For Facile Separationmentioning
confidence: 99%
“…In the last few decades, magnetic nanoparticles have been employed as an effective replacement for heterogeneous catalyst supports because they have many advantages such as ease of availability, chemical stability and simple preparation . Most importantly, Fe 3 O 4 ‐supported metal catalysts can be separated from a reaction system using an external permanent magnet.…”
Section: Introductionmentioning
confidence: 99%